2007
DOI: 10.1097/01.aog.0000275284.24298.23
|View full text |Cite|
|
Sign up to set email alerts
|

Group Prenatal Care and Perinatal Outcomes

Abstract: OBJECTIVE-To determine whether group prenatal care improves pregnancy outcomes, psychosocial function, and patient satisfaction and to examine potential cost differences.METHODS-A multisite randomized controlled trial was conducted at two university-affiliated hospital prenatal clinics. Pregnant women aged 14−25 years (n=1,047) were randomly assigned to either standard or group care. Women with medical conditions requiring individualized care were excluded from randomization. Group participants received care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
430
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(448 citation statements)
references
References 27 publications
12
430
5
Order By: Relevance
“…The CPM has been studied, with positive clinical outcomes. [7][8][9] This model correlates well with the climate of transformational practice change suggested by the Institute of Medicine. Our group visit care model was implemented in the residency training at the Concord Hospital Family Health Center clinical practice.…”
Section: Methodssupporting
confidence: 68%
“…The CPM has been studied, with positive clinical outcomes. [7][8][9] This model correlates well with the climate of transformational practice change suggested by the Institute of Medicine. Our group visit care model was implemented in the residency training at the Concord Hospital Family Health Center clinical practice.…”
Section: Methodssupporting
confidence: 68%
“…Randomized controlled trials demonstrating improved outcomes among women and newborns after participation in group ANC compared with standard ANC have been conducted in the United States7, 8, 9, 10, 11, 12 and Sweden,13 which the World Bank classifies as high‐income economies, and Iran,14, 15 which is classified as an upper middle‐income economy. Published benefits include increased uptake of postnatal family planning services, greater gestational age at birth and birth weight, lower incidence of sexually transmitted infections, healthier maternal weight trajectories, fewer depressive symptoms, and increased satisfaction with care 16.…”
Section: Introductionmentioning
confidence: 99%
“…Group prenatal care may be one of the strategies nurses can employ to reduce stress . Ickovics et al (2007) demonstrated that group prenatal care which includes physical assessment, education and skills building, and support through facilitated group discussion, reduced the incidence of preterm birth when compared to women who received individual prenatal care. Group prenatal care reduced the stress and the effects on maternal and fetal endocrine stress response, minimizing the incidence of preterm birth.…”
Section: Implications For Practicementioning
confidence: 99%